Sexual Assault;Our experience at One Stop Shop for Women and Girls, National Obstetric Fistula Centre, Abakaliki , Ebonyi State. South East Nigeria: A retrospective study - Onyinye, Anyanwu, Uchenna; C, Uro-Chukwu, H.; A, Obuna, J. (Jour Med Resh and Health Sci, 2022)
Sexual assault is a global health challenge. It refers to all forms of sexual contact or behavior that occurs without explicit consent of the victim. This was a retrospective review of cases of gender based violence (GBV) who presented at the one-stop-centre for females over a sixteen months period (Nov 2020-Feb 2022) from which cases of sexual assault was selected and studied(subjects). Prevalence of 66.3% was obtained for sexual assault out of a total of 86 GBV patients who presented in the study period. The mean age of subjects was 12.77+5.4(1-23years), Fifty (87.7%) were of the pediatrics age group and 7(12.3%) were adults. Fourty seven (82.5%) belonged to the low socioeconomic class while timely presentation (<72hours) occurred in only 14(24.6%). Rape was the commonest form of sexual assault 58(98.2%). The finding indicates a high prevalence of sexual assault. Concerted effort needs to be made to reduce its occurrence.